A forest planting plan for the waste land of a Kansas farm - Willard, Charles (My University, 1908)
Introduction: In going over our upland Kansas farms, one is invariably struck with the amount of more or less waste land upon them. Stony hillsides, washed gullies, sloughs, small, frequently flooded creek bottoms, and hillside fields which are washed and gullied until they are mere clay banks, are some of the places of this sort.
Citation: Willard, Charles. A forest planting plan for the waste land of a Kansas farm. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Forests; Kansas; Farming; Waste Lands; Graduating theses; Senior theses; Theses